Peritibial fascial infiltration block and selective saphenous nerve block for postoperative analgesia of ankle fracture surgery - Altıparmak, Başak; Çiftçi, Bahadır; Korkmaz Toker, Melike (Edizioni Minerva Medica, 2022)
Over the last decade, increased availability of ultrasound (US) guidance has led to the description of innumerable novel fascial plane blocks. As a result, an international Delphi Consensus study was conducted to standardize nomenclature of regional anesthetic techniques of the abdominal wall, paraspinal, and chest wall regions.1 Although some clinicians claim the daunting number of novel approaches are needless, especially easily applied techniques may provide certain advantages such as less risk of complications, less consumption of time and sources.
Keywords: Ankle Fracture Surgery; Postoperative Analgesia; Peritibial Fascial